EXPLORING FAMILY-OWNED BUSINESSES IN THE STATE OF HIDALGO, MEXICO - Calzada, Martin Aubert Hernandez; Moheno, Jessica Mendoza; Hernandez, Blanca Cecilia Salazar (European Scientific Journal, ESJ, 2015)
The starting point of this research focuses on a sample of familyowned businesses in the state of Hidalgo, Mexico. We present the preliminary results of the research project entitled "Management of Governance in Family-Owned Business", in which a survey was applied to 167 firms in the state of Hidalgo. The research has a descriptive and exploratory nature and aims to obtain a general assessment of the reality of these companies, in order to get a diagnosis of these firms and provide a set of future research questions. The research took into account various aspects, e.g., a) Form and activity of the company, b) Management of the company, c) Current property, d) Incorporation of the company family, e) Management board, f) Family council, g) Family heritage business assets, h) Succession i) Transfer of ownership of the company, and j) Protocol family. The main findings are the poor presence of governance structures in family business, and the lack of planning for the continuity of such businesses.